EKSPLORATORI TUJUAN MANAJEMEN KEUANGAN BISNIS HIJAU - Djoko Wintoro (University of Merdeka Malang, 2012)
Companies were facing growth pressure to transform into green business. They needed green management aswell as green finance to guide the implementation of green business. This research explored the objectives ofgreen financial management. By sending questionnaires to Finance Director of Indonesian companies, thisresearch found that the objective of green finance included three objectives which were to maximize shareholderwealth, maximize social wealth, and sustain natural resources.